In vitro controlled drug release from contact lenses materials under physiological ocular tear flow - Paradiso, P. (2015)
Poster presented at the 9th World Meeting on Pharmaceutics, Biopharmaceutics and Pharmaceutical Technology. Lisbon, 31 March-3 April 2014.